Carbohydrate Counting: Meals for Diabetes - Cassie Rowe; Jamila R. Lepore; Wendy J. Dahl (EDIS, 2013)
“Carb” counting is a way to plan meals to help you maintain target blood glucose levels. Certain foods contain carbohydrate, and these are the foods that most influence your blood glucose. Your body needs carbohydrate in just the right amount. Not enough carbohydrate can lead to low blood glucose (hypoglycemia). Too much carbohydrate can lead to high blood glucose (hyperglycemia). This is why carb counting is a great tool to understand and practice because it can help you control your blood glucose and still give you the freedom to make varied food choices. This 4-page fact sheet was written by Cassie Rowe, Jamila R. Lepore, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, March 2013.